E-Assessment as a Vector for Identifying and Increasing the Validation of Advice Within Professional Organizations - Aichi, Yassir; Bassiri, Mustapha; Benmokhtar, Said; Belaaouad, Said (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The particularity of E- Assessment is that it allows to combine the assessment of personality with that of personal and interpersonal values. It is this joint assessment that makes all the richness and interest of digital assessment for human resources professionals in terms of recruitment, career management, professional orientation and assessment of soft skills.The platforms dedicated to evaluation cover several families: behavioral tests or personality tests, aptitude tests and value questionnaires. They have the particularity to measure with a certain precision dimensions clearly denied by the editor, in connection with scientific concepts. Then they statistically compare the results to a standard and a reference population. In order to assess the impact of E- Assessment t, we opted during this study at SOSIE 2nd Generation for a digital HR tool that meets the current requirements of human resources professionals for assessment in international contexts. Indeed, the work was carried out on the content of the items, the dimensions, the descriptive and interpretation reports through a reading in terms of percentiles, common behavior styles for a population of Moroccan professionals operating in various sectors of activity.